Jiak - Tan, Angelica Ying Ying (2014)
Snippets of daily life all encompassed into a transcendence of history. Personal to every individual, these nostalgic memories are what make a person and place so unique. Singapore has developed so rapidly that places, tradition and culture, imperative to our foundation, is diminishing rapidly.